The United States as the Trade Partner of Poland in te Context of the Transatlantic Trade and Investment Partnership (TTIP) - Marks-Bielska, Renata; Lizińska, Wiesława; Serocka, Izabela (Olsztyn Economic Journal, 2014)
Evaluation of the importance of the USA as the trade partner of Poland is the main objective of the paper, based on the changes in the value of trade during the years 2000-2012 and changes in the structure of trade during the years 2008-2012. The data from the Statistical Yearbooks of Foreign Trade published by the Central Statistical Office was used. The potential for foreign trade growth was illustrated using the simplified analysis based on the gravity model of foreign trade concept. Gradually increasing value of Polish trade with the USA (the average growth rate 9.8%, EU-15 countries 13.1%). Polish exports are characterised by a higher than imports growth rate (USA - exports growth by 12.5%, imports 9.2%, EU-15 - exports 15.1%, imports 11.6%). Trade is strongly dominated by position of one group of products (over 30% share in both exports and imports). The potential of trade is poorly exploited currently. Trade was focused mainly on the countries situated in the close neighbourhood (mainly the EU countries with the domination of Germany).